Standard specification for seamless brass tube [Metric]
This specification covers seamless round and rectangular including square copper alloy tube in straight lengths. This specification is under the jurisdiction of ASTM Committee B05 on Copper and Copper Alloys and is the direct responsibility of Subcommittee B05.04 on Pipe and Tube.